Rancang Bangun Aplikasi Pembelajaran Tajwid Menggunakan Metode Agile Berbasis Android - Mulia, Muhammad Aprialdi; Djamaludin, Djamaludin; Syam, Syahriani (JURNAL ILMIAH FAKULTAS TEKNIK, 2024)
Background: The lack of time for lessons on Tajweed in official or formal schools is due to the fact that the subject matter of the study of Tajweed is quite a lot of material and will not be enough to be completed with only Islamic-Religious Education subjects. For example, the initial introduction to the science of tajwid, the place where letters are issued (makhroj), the nature of the letters, the law of nun sukun/tanwin, and many other materials. Methods: In this study, researchers used the SDLC (Software Development Life Cycle) system development method. The type of SDLC used is the Agile Method. Research Results: In this study using black box testing, which shows that the application of recitation learning media is able to make students interested in learning tajwid. Conclusion: Based on the results of the implementation and the results of the tests that have been carried out, the authors conclude that the system or application of this recitation learning can run as expected.   Keywords: Tajweed, Al-Qur'an, Applications, Learning, Android.